Strategi Segmentasi, Target Dan Posisi Pasar Klinik Aestetik di RS Multazam Medika - Ni’matunnisa, Evie (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2020)
Aesthetics Clinic is a product that began to be developed, both independent clinics or in hospitals. With the growing technology used, it makes people more concerned about skin health so that beauty service products can be an alternative business strategy that can be developed and become a profit for private hospitals today. With the increasing competition between hospitals, the addition of aesthetic clinic services at Multazam Medika Hospital is expected to bring something new in the development of hospital marketing products. This study uses a descriptive analysis methodology whose results will be input for hospitals in determining business strategies.